The city and education: a study on pedagogical practices and citizen formation - Marina Zaidan Nery; Carliane Maria do Carmo Lins da Natividade; Viviane de Bona (Universidade Estadual de Alagoas, 2021)
Non-formal education is a space for training and learning knowledge for life, a space that is socio-political, cultural and pedagogical. In this sense, NGOs and social movements are the most common places where it occurs. Based on this premise, the present article aimed to identify, from the perspective of the young participants, the effectiveness of the pedagogical practices of the Youth and Urban Space course, in an NGO located in the city of Recife, in the state of Pernambuco. As a methodology, qualitative research was used, having as instruments the systematic observation and interviews with nine peripheral young people participating in the course. In the analysis of the collected data, we used content analysis according to Bardin (2011).Based on the monitoring of training meetings and interventions carried out in their communities, we identified that NGOs usespedagogical tools to conduct workshops, projects, interventions, self-assessment and class evaluation. The systematicity and intentionality of social educators, when carrying out the meetings, was latent during the researched period and very significant for the effectiveness of learning. Furthermore, through the interviews, we identified the young person's view of the course and non-formal education, in this path, we realized how some young people, for example, did not know how to distinguish the practices carried out at school and at the NGO, while others noticed a great difference. In addition, we seek to verifythe efficiency of the course in the citizen education of the young participants, mainly through the engagement generated, as well as their awareness of the space where they live. Therefore, weverify the importance of non-formal education in the lives of these peripheral young people, since it provides theoretical and practical knowledge about the right to the city and the possibilities of intervention in their communities, expanding their critical look at the space where they live, as also, the pedagogical practices used during the course, brought freedom, criticality and above all autonomy to them, helping them to propose effective projectsandexpanding the knowledge they had.